Soil factors enhance amino acid and peptide accumulation in tuberous roots of Pseudostellaria heterophylla - Zheng, Huiyong; Chen, Hong; Zheng, Meixia; Niu, Yuqing; Zhang, Jiajia; Luo, Wenbao; Zhu, Yujing; Su, Hailan; Zhu, Yanming (Frontiers in Plant Science, 2025)
IntroductionPseudostellaria heterophylla (PSH) is a renowned medicinal and culinary plant. However, soil-related factors limiting in the improvement of its yield and quality in practice remain poorly understood.MethodsWe sampled two PSH varieties and their associated rhizosphere soils from two sites in Ningde City, Fujian Province, China, including Chouling village (Z) and Wuyang village (W), to analyze the basic soil physicochemical properties, soil bacterial communities, and untargeted metabolomics of both soils and tuberous roots samples. ResultsOur results showed that the rhizosphere soil at site Z had significantly higher concentrations of calcium (Ca), magnesium (Mg), manganese (Mn), available phosphorus (AP), and available potassium (AK), but a lower concentration of alkaline hydrolyzable nitrogen (AN). Soil AN and AK were identified as key determinants of bacterial community structure, showing negative and positive correlation with numerous microbial phyla and genera, respectively. Site Z exhibited higher abundances of functional bacterial phyla, including Desulfobacterota, Nitrospirota, and Elusimicrobiota, as well as dominant genera of Acidobacteriota. Amino acids and peptides (AAs) were the most abundant class of differential metabolites (DMs) in both the rhizosphere soil and tuberous roots of PSH. The accumulation of AAs in tuberous roots was positively correlated with soil pH, electrical conductivity (EC), and potassium (K) levels, but negatively correlated with AN. Furthermore, specific microbial taxa and soil DMs at site Z were positively associated with AA abundance in the tuberous roots. DiscussionThese findings suggest that appropriate soil nitrogen levels coupled with relatively high potassium availability, pH, and EC conditions are conducive to AAs accumulation in PSH tuberous roots.